196k views
4 votes
Given that g(x)=x+3 and h(x)=x sqared calculate g-1(7)

User Yossi
by
5.1k points

1 Answer

3 votes

In this case, we know
g(x) = x + 3, and we are trying to find
g^(-1)(7).


So, we will need to find
g^(-1)(x). Let's do that now:


y = x + 3

  • Replace
    g(x) with
    y. This is just simple substitution, nothing major has happened yet.


x = y + 3

  • Switch
    x and
    y. This is simply part of the process of finding the inverse function


y = x - 3

  • Solve for
    y


g^(-1)(x) = x - 3

  • Replace
    y with the notation for the inverse function

Now, we are going to solve for when
x = 7. To do this, simply "plug in" 7 for
x in the inverse function.


g^(-1)(7) = 7 - 3 = \boxed{4}


Our answer is 4.

User Hadiya
by
5.9k points